Relíquias da casa velha: literatura e ditadura militar, 50 anos depois - Tânia Pellegrini (Estudos de Literatura Brasileira Contemporânea)
This essay tries to relate specific actions of the military regime in the field of culture to the effective consolidation of a cultural industry in Brazil. It is based on a more or less alleatory search in newspapers and magazines of the period. It also revisits the critical literature about the subject and retakes my own previous researches. The assumption is that the cultural industry consolidation has produced in a tensioned way, significant modifications in the preexistent matrixes of Brazilian fiction, mainly in its themes, which translated the mallaise and perplexity of those difficult years, as well as their derivations to this day.